Synthesis of CuMoS micro‐rods material as efficient bifunctional electrocatalyst for overall water splitting - Kalusulingam, Rajathsing; Selvam, Mathi; Mikhailova, T. S.; Popov, Y. V.; Khubezhov, S. A.; Pankov, I. V.; Myasoedova, Tatiana N. (ChemistrySelect (Weinheim), 2023)
In oxygen evolution reactions (OER) metal sulfides are the subject of extensive research. Copper‐molybdenum sulfides (CuMoS) that can be made a simple hydrothermal treatment are designed to reduce catalyst costs even more. Here, we demonstrate that binder free electrode composed of micro‐rod structure copper‐molybdenum sulfides on nickel foam (CuMoS/NF) can be employed as an active and robust bifunctional electrocatalyst for water splitting. CuMoS/NF catalyst displays an overpotential for OER of 358 mV (121 mV dec−1) and HER of 129 mV (101 mV dec−1) at current density of 10 mA cm−2. CuMoS/NF is stable for 60 hours with potential deviations in OER and HER of 2.8 % and 3.2 %, respectively. The active bifunctional CuMoS/NF electrode combination helps to fabricate a water electrolyser with 10 mA cm−2 current density at 1.65 V. CuMoS/NF//CuMoS/NF shows good stability over 60 hours with a potential deviation of 2.7 %. The earth‘s abundant non‐precious metal‐based electrode, and solar cell delivered continuous hydrogen and oxygen (1.65 V), making it possible to produce a significant quantity of hydrogen at a low‐cost and on a large‐scale. Bimetallic Copper molybdenum sulfide microrod electrocatalyst was prepared through hydrothermal method. As prepared CuMoS show highly catalytic activity for electrochemical reaction OER and HER in basic 1.0 M KOH alkaline medium. Superior OER activity with a lower overpotential of 358 mV at 10 mA cm−2 and Tafel slope of 121 mV dec−1. Lower HER overpotential of 129 mV at 10 mA cm−2 and a Tafel slope of 101 mV dec−1. CuMoS based two electrode water splitting exhibited a cell voltage of 1.65 V at 10 mA cm−2 and CuMoS exhibited an prolong stability for 60 hours at 10 mA cm−2.